Portugal : Seventh Review Under the Extended Arrangement and Request for Modification of End-June Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2013)
Portugal's program implementation is on track despite difficult economic conditions and significant legal challenges. The markedly weaker economic outlook provides a strong case for recalibrating the program's fiscal targets. This strong adjustment effort needs to be consolidated by sustained fiscal structural reforms. Continued vigilance is warranted to secure financial stability. A more competitive economy for sustainable recovery requires addressing nominal rigidities forcefully. Program success also hinges on continued external support and effective crisis management policies at the euro area level.